HEIGHT - DEPTH (BREADTH) RELATIONSHIP OF SHELL IN THE BACKWATER OYSTER Crassostrea madrasensis (PRESTON) OF THE COCHIN HARBOUR - NAIR, N UNNIKRISHNAN (Fishery Technology, 2017)
A study of the height-depth relation in the Indian backwater oyster Crassostrea madrasensis (Preston) was carried out. The plot of height against depth showed an exponential trend and a relationship of the form H = ADB. Plot of hejght against depth also showed larger deviations in height for oysters with greater depth. Analysis showed that variations in height does not result in corresponding variations in depth, particularly in oysters with increased height.